2013
DOI: 10.1093/nar/gkt1171
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Hfq-RNA interaction surfaces using tryptophan fluorescence quenching

Abstract: Hfq is a posttranscriptional riboregulator and RNA chaperone that binds small RNAs and target mRNAs to effect their annealing and message-specific regulation in response to environmental stressors. Structures of Hfq-RNA complexes indicate that U-rich sequences prefer the proximal face and A-rich sequences the distal face; however, the Hfq-binding sites of most RNAs are unknown. Here, we present an Hfq-RNA mapping approach that uses single tryptophan-substituted Hfq proteins, all of which retain the wild-type H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
78
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(86 citation statements)
references
References 65 publications
8
78
0
Order By: Relevance
“…The CTD has been proposed to stabilize RNA·Hfq complexes via direct interactions with sRNAs (19,36,57) owing to the slightly weaker binding of sRNAs in the absence of the CTD (10, 25), which we have recapitulated (Table 1). However, the data presented in this paper do not support this stabilization model because the CTDs do not increase the affinity of RNA oligomers (A18-FAM and D16-FAM) ( Table 1) and actually decrease the affinity of RNA stem loops (beacon and minRCRB) ( Table 1).…”
Section: Discussionsupporting
confidence: 55%
“…The CTD has been proposed to stabilize RNA·Hfq complexes via direct interactions with sRNAs (19,36,57) owing to the slightly weaker binding of sRNAs in the absence of the CTD (10, 25), which we have recapitulated (Table 1). However, the data presented in this paper do not support this stabilization model because the CTDs do not increase the affinity of RNA oligomers (A18-FAM and D16-FAM) ( Table 1) and actually decrease the affinity of RNA stem loops (beacon and minRCRB) ( Table 1).…”
Section: Discussionsupporting
confidence: 55%
“…It binds uridine-rich sRNAs using its proximal face (Mikulecky et al 2004;Sauer and Weichenrieder 2011;Panja et al 2015) and the outer rim (Sauer et al 2012), and it binds mRNAs containing (ARN) n sequence motifs using its distal face (de Haseth and Uhlenbeck 1980;Link et al 2009). However, recent studies have suggested that other modes of RNA interactions with Hfq are also possible, both in Escherichia coli (Zhang et al 2013;Małecka et al 2015;Schu et al 2015) and in Gram-positive bacteria Robinson et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the crystal structure of Escherichia coli (Ec) Hfq bound to A 15 RNA showed polyadenosine binding to the opposite or "distal face" (Link et al 2009). Unlike the proximal face, the distal face of Ec Hfq has three distinct nucleobase binding sites per protomer, originally called the A-R-N motif, where A is an adenine-only binding site, R is a purine-nucleotide specificity site with a strong preference for adenine (Robinson et al 2014), and N is a nondiscriminatory solvent-exposed nucleotide that is the likely distal-face RNA entry and exit location. As a consequence of this motif, a maximum of 18 nt can readily occupy the distal face of Ec Hfq.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescence polarization-based Hfq-RNA binding measurements also indicate that magnesium plays a role in RNA binding to the proximal face of the protein. Intriguingly, RNA-Hfq tryptophan fluorescence quenching assays (Robinson et al 2014) suggest strongly that Lm Hfq is a more promiscuous RNA-binding protein than Hfq proteins from other Gram-positive bacteria.…”
Section: Introductionmentioning
confidence: 99%